The Adoption of Leadership in Managing the Skilled Blue Collar Workers in the Automotive Industry in Malaysia In Parallel to the Industry 4.0 - Hwa, Eng Poh; Hamid, Syaiful Rizal; Chew, Boon Cheong (International Journal of Psychosocial Rehabilitation, 2020)
There are four stages of industrial revolution (Industrial 1.0 to Industrial 4.0) which trigger a technological transformation that will gradually alter our living and working styles. One of the significant industrial revolutions, Industry 4.0 Transformation Drivers is concerned about the knowledge and skill for the future in retaining talent and producing future workforce by taking advantage of the opportunities of this transformation. The research aims to explore the adoption of leadership in managing the skilled workers in the automotive industry in Malaysia in parallel to the Industry 4.0. The adoption of effective leadership is able to contribute positively to the talent retention among the skilled blue collar workers in the automotive industry in Malaysia.